USING ROUNDTABLE TECHNIQUE IN TEACHING WRITING HORTATORY EXPOSITION TEXT - Fidyati, Lailatul; Rufinus, Albert; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The objective of this research was to find out the effectiveness of Roundtable technique in improving students’ Hortatory Exposition Text writing ability and its effectiveness to improve students’ writing in terms of content, grammar, and organization. The research was conducted in SMAN 1Sungai Raya through quasi experimental research method. The subjects of the research were the eleventh grade students of XI IPA 1 and XI IPA 5. The data analysis showed that Roundtable technique is effective in improving students’ ability in writing Hortatory Exposition Text. It was also found that, Roundtable was also effective to improve students’ ability in terms of content and grammar; however it was not highly effective to improve the organization aspect. Keywords: Roundtable technique, Writing, Hortatory Exposition Text Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui efektivitas dari tehnik Roundtable dalam meningkatkan kemampuan siswa menulis teks Hortatori Eksposisi dan efektivitas dari tehnik Roundtable untuk meningkatkan kemampuan siswa dalam menulis, dilihat dari segi isi, grammar, dan organisasi. Penelitian dilakukan di SMAN 1 Sungai Raya melalui metode penelitian quasi experimental. Subyek dari penelitian ini adalah siswa kelas XI IPA 1 dan XI IPA 5. Analisis data menunjukkan bahwa tehnik Roundtable efektif untuk meningkatkan kemampuan siswa dalam menulis teks Hortatori Eksposisi. Ini juga ditemukan bahwa, tehnik Roundtable juga efektif untuk meningkatkan kemampuan siswa dilihat dari segi isi dan grammar; meskipun tehnik Roundtable tidak sepenuhnya efektif untuk meningkatkan aspek organisasi. Kata kunci: Tehnik Roundtable, menulis, Teks Eksposisi Hortatori